Diagnostic Accuracy of Fine Needle Aspiration Cytology in Thyroid Swellings - Bista, M; KC, Toran; Regmi, D; Maharjan, M; Kafle, P; Shrestha, S (Journal of Nepal Health Research Council, 2011)
Background: Proper management of the disease depends upon accurate diagnosis. Fine Needle Aspiration Cytologyhas become the investigation of choice because of its high accuracy, simplicity, minimal-invasiveness, quick result andreliability.Methods: All the patients with thyroid disease, irrespective of age and gender, who underwent thyroid werestudied. These patients had their fine needle aspiration Cytology was done in our centre. Detailed history, physical examination, routine investigations, radiological investigations (including CT scans when needed), hormonal assay, (T3, T4, TSH ), ultrasound of neck and FNAC were done. Pre- operative fine needle aspiration results were compared with histopathology results of operated specimen and then analyzed statistically to assess the sensitivity, specificity and accuracy of the result.Results: There were total of 51 patients. Age ranges from 21 to 62 years. The study duration was from May 2006 to February 2011. Out of 51 patients, 82.35% (n=42) were females and 17.64% (n=9) were males. In 43 patients, FNAC showed benign lesions, of which 40 were true negative (TN) and three false negative (FN), which on histopathology reported malignancy. Remaining eight cases were diagnosed as malignancy on histopathology of which seven cases were true positive (TP), one case of false positive (FP) was detected in our study. Over all Sensitivity was 70% and specificity was 97.5% and accuracy of FNAC was 92.1%.Conclusions: FNAC should be performed in all cases of thyroid nodules because of its high sensitivity and specificity to differentiate benign from malignant lesions and counsel the patient as well as plan surgery accordingly. Expenditure, time and the hassle of revision surgery is minimized by the pre operative FNAC report.Keywords: fine needle aspiration cytology, histopathology, sensitivity, specificity, thyroid swellings.